(untitled) (TEST Ticontre. Theory Text Translation, 2020)
The article proposes a comprehensive analysis of the neapolitan review «Incognita» (1982-1984), directed by the poet Giancarlo Majorino. Le review includes very different critical perspectives, from which the necessity to make an assestment on the previous decade, still poignant in some problematic issues, emerges. In the first part the analysis focuses on Majorino’s activity as curator of a poetry anthology in the Seventies, evaluating some of his opinions whose persistence may be found in his direction of the review. In «Incognita»’s analysis are also some attempts to define characteristics and importance of a marginalized and underlying literature, in opposition to a cultural elite which controls the editorial market. The second part the study focuses on some poetic texts, different in style and in the authors’ generation. Furthermore, it is evaluated the space dedicated to authors tied to the territory and some theorical propositions regarding style and foreign authors’ critical reception. In the third part the article recounts the specialized studies on the role occupied by the public in reading the poetic text: particularly the research conducted by Giorgio Majorino through the lens of cognitive psychology. Lastly, this research tries to present the review’s strong points and limitations: even with the wide variety of its propositions, the lack of a better and adversarial dialogue between the different theorical ideas proposed through «Incognita»’s activity is hard to ignore. It is also for this reason that the question emphazised in the review’s title doesn’t seem to find an answer.